Peranan R & D Dalam Industri Container Dan Packaging - Gatoet Soedomo (Jurnal Kimia dan Kemasan, 1979)
The role of R & Din the field of packaging and container industry is to investigate all aspects in connection with packaging and container problem, with the purpose to get the optimum benefit.R & D activities including all aspects from software problems to hardware problems. The efforts of R & D can be divided into : self initiative R & D, collective R & D, and order R & D.